Quantum-like Qualia hypothesis: from quantum cognition to quantum perception - Tsuchiya, Naotsugu; Bruza, Peter; Yamada, Makiko; Saigo, Hayato; Pothos, Emmanuel M. (Frontiers in Psychology, 2025)
The recent explosion in theories of consciousness, which aim to link subjectivity and physical substrates, require a better characterization of mathematical structure of quality of consciousness, or qualia.In traditional and intuitive models of qualia, a particular quale is assumed to be a point in a high dimensional space.Such models assume that qualia exist independent of measurements, but they are incompatible with the findings that qualia are generally affected by measurements.To account for how the measurement can affect qualia, a Quantum-like Qualia (QQ) hypothesis proposes a mathematical structure employed in quantum theory.We will outline how QQ can be tested with various experimental paradigms, building on the successful quantum cognition framework.